POLA PERILAKU SEDENTARI MERUPAKAN FAKTOR RESIKO KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR DI KOTA YOGYAKARTA DAN KABUPATEN BANTUL - , Andi Imam Arundhana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: According to Basic Health Research (Riskesdas) 2010 the prevalence of obesity in Yogyakarta was 78% in 2010. Increasing prevalence of obesity in school children is mainly related to sedentary activities and decreasing medium-high physical activities. Objective: To find out whether sedentary behavior was risk factor for obesity in school children and identify level of its contribution. Method: The study used case control design. Population consisted of elementary school (either state or private) children of grade 1-5 at Yogyakarta and Bantul. The selection of school during screening phase was based on Probability Proportional to Size (PPS) method. The choice of cases in children diagnosed obese during screening phase used simple random sampling supported with random table tool and matching of school. Based on sample basic calculation there were 488 samples consisting of 244 cases and 244 controls. Data of physical activities were obtained through modified questionnaire on childrenâs physical activities (CPAQ). Data were processed using software of Epidata v 3.1 and STATA v.11. Analysis used univariate, bivariate, and multivariate analysis with t test, anova, and logistic regression. Result: Duration of sedentary behavior in obese students was longer than those not obese with average difference 49.81 minutes/day (p<0.01). The result of chi square analysis showed sedentary activities had significant correlation with the incidence of obesity with OR=6.93 (95% CI: 4.56-10.54). Based on types of sedentary activities, there was significant correlation for category of screen based and sitting around (p<0.05). Conclusion: Sedentary behavior was risk factor for the incidence of obesity in elementary school children. Average duration of sedentary activities of obese children was higher than those not obese. Based on residency, average duration of sedentary activities of obese children in urban area was higher than those living in rural area.